SOSIALISASI CUCI TANGAN PAKAI SABUN DI SDN 24 MEMBALONG DESA BANTAN KABUPATEN BELITUNG - Muhammad Galang Asshiddiqi; Dila Charisma (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
SOCIALIZATION OF HAND WASHING WITH SOAP AT SDN 24 MEMBALONG BANTAN VILLAGE, BELITUNG DISTRICT. Encouraging the community, especially the school community, to adopt clean and healthy living habits (PHBS) is very important. Schools have the potential to spread diseases in addition to serving as places of learning if the student body fails to uphold PHBS ideals. Evidently connected to PHBS is the rise of illnesses that frequently affect school-age children (6â€“10 years old).Â Â As a result, teaching these principles might begin with something as simple as hand washing. Teaching people to wash their hands properly can be done by using a health promotion outreach method that is regularly assessed for its effectiveness as a way to build community capacity through a process of learning that is modeled after School Health Enterprise (UKS) programs. The overall goals and benefits of this events are to give Membalong 24 Elementary School students, Belitung Regency with an understanding of how to wash their hands cleanly using soap, so that students can apply clean and healthy living habits independently in their daily lives. Counseling and demonstration approaches were employed to complete this exercise, along with image media, posters/leaflets, and music. The outcomes of this activity reveal that pupils have a great knowledge of the affects and benefits, as well as how to clean their hands with soap.